Web-Based Learning: A Bridge to Meet the Needs of Canadian Nurses for Doctoral Education - Kurucz, Susan; Lim, Angie; Rietze, Lori; Swamy, Mindy (Canadian Journal of Higher Education, 2015)
Canada does not have enough nurses with doctoral degrees. Such nurses fill important roles as researchers, educators, leaders, and clinicians. While a growing number of Canadian universities offer doctorate degrees in nursing, most institutions have only traditional on-campus programs, posing barriers for nurses who reside in places geographically distant from those institutions or who require more flexibility in their education. We describe our experiences as the inaugural cohort of the doctoral program by distributed learning at the University of Victoria School of Nursing. Since 2011, we have used a variety of electronic modalities and participated in several very short on-site intensives. Our experience indicates that distributive learning modalities improve access and deliver academically rigorous programs.